Contraceptive use and method preference among HIV-positive women in Amhara region, Ethiopia - Kefyalew Addis Alene; Kendalem Asmare Atalell (BMC, 2018)
Abstract Background Providing preferred methods of contraceptive for HIV-positive women and avoiding unintended pregnancy is one of the primary means of preventing mother to child transmission of HIV. This study assessed the prevalence of contraceptive use and method preference among HIV-positive women in Amhara region, Ethiopia. Methods A cross-sectional survey was conducted among HIV-positive women in three referral hospitals of Amhara region. Data were collected by interviewing HIV-positive women using a pre-tested and structured questionnaire. A binary logistic regression model was used to identify factors associated with contraceptive use, and odd ratio with 95% confidence interval (CI) was calculated to measure the strength of association. Results A total of 803 women living with HIV (with a response rate of 95.4%) were interviewed. The mean age of the study participants was 32.2 years (SD ± 6.2 years). The prevalence of current contraceptive use was 30.3% (95% CI: 27.0-33.7%). The preferred and most commonly used contraceptive methods were injectable (42.8%) and male condom (32.9%). Younger age group (15-24 years) (AOR = 9.67; 95%CI: 3.45, 27.10), one or more number of living children (AOR = 4.01; 95%CI: 2.07, 7.79), HIV diagnosis > 2-4 years (AOR = 2.37; 95%CI: 1.10, 5.08), and having high CD4 count > 500 cell/ul (AOR = 3.25; 95% CI: 1.42, 7.44) were significantly associated with contraceptive use. Conclusion The prevalence of contraceptive use among HIV-positive women in Amhara region referral hospitals is low, which suggests a high risk of unintended pregnancy. Injectable and male condoms are the most preferred type of contraceptive methods. Thus, it is better to integrate these contraceptive methods with ART clinic.